Dynamics of a fractional order predator-prey model with intraguild predation. (2nd October 2019) - Panja, Prabir
ABSTRACT: In this paper, a fractional order predator–prey mathematical model has been developed. In this model, the concept of intraguild predation has been introduced. It is assumed that intermediate predator consumes only prey and intraguild predator consumes prey as well as intermediate predator. Also, intraspecific competition of prey, intermediate predator and intraguild predator has been considered. Uniqueness, boundedness and non-negativity of solutions of our proposed model have been discussed. Different possible equilibrium points are determined and the stability of our proposed model around these equilibrium points has been studied. It is found that fractional order system can show some interesting dynamics of our proposed model. Finally, some numerical simulation results have been presented to verify our theoretical findings.